Adult Day Centers as Partners in Baccalaureate Nursing Dementia Education. - DeBrew, Jacqueline Kayler (Creative Nursing, 2026)
This pilot study explored how adult day centers can serve as transformative clinical learning environments for nursing students to learn dementia care. Fourteen students in an accelerated Bachelor of Science in Nursing program participated in two clinical experiences at community-based memory care centers and then submitted reflective journals. Guided by Mezirow's Transformative Learning Theory, analysis revealed that students reported finding the experiences meaningful, challenging their prior assumptions about dementia, and enhancing their empathy for both individuals with dementia and their caregivers. Themes identified were Positivity, Appreciation for Caregivers, Communication Skill Development, and Understanding the Stages of Dementia. By observing the lived experience of people with dementia in a relaxed, community setting, student feedback challenged the prevailing clinical norms that privilege acute care and simulation. The findings suggest that adult day centers can be powerful sites for deep learning in nursing education.